Biomolecular Aspects of Second Order Limit Language - Muhammad Azrin, Ahmad; Nor Haniza, Sarmin; Mohd Firdaus, Abdul-Wahab; Fong, Wan Heng; Yuhani, Yusof (Penerbit UTM Press, 2018)
The study on the recombinant behavior of double-stranded DNA molecules has led to the mathematical modelling of DNA splicing system. The interdisciplinary study is founded from the knowledge of informational macromolecules and formal language theory. A splicing language is resulted from a splicing system, in which different types of splicing langauges have been researched previous, namely adult/inert, transcient and first order limit language. Recently, second order limit language has been extensively explored from the first order limit language. Therefore, in this paper, a laboratory experiment was conducted to validate the existence of a second order limit language. To accomplish it, an initial strand of double-stranded DNA, amplified from bacteriophage lambda, was generated through polymerase chain reaction to generate thousands of copies of double-stranded DNA molecules. A restriction enzyme and ligase were added to the solution to complete the reaction. The reaction mixture was then subjected to polyacrylamide gel electrophoresis to separate biological macromolecules according to their sizes. A mathematical model derived at the early study was used to predict the approximate length of each string in the splicing language. The results obtained from the experiment are then used to verify the mathematical model of a second order limit language. This study shows that the theory on the second order limit language is biologically proven hence the model has been validated.